Conhecimentos, habilidades e atitudes do moderno profissional da informação nos novos mercados com ênfase na atuação em empresas - Paula, Micaele Marques de (Brasil, 2019)
The research in question is an exploratory and descriptive research, based on a literature review, aiming to select articles and academic works in the areas of Librarianship and Information Science to identify what knowledge, skills and attitudes (CHA) are respondents to the modern information professional in the new markets. It identifies the characteristics of the modern information professional (MIP) and its context of action, raises the knowledge, skills and attitudes of this professional, classifying their competencies from the CHA directed to the performance in companies. After analyzing the research on the CHA with the labor market, aimed at companies, a CHA proposal for IPM in companies is prepared, to be validated by specialists via e-mail, through an evaluation tool, with the objective of validating the agreement and intensity of the relevance of the librarian's competences in relation to their performance in companies. Given this, it is found that the professional who has knowledge, skills and attitudes compatible with their role, can fulfill their role and show their professional potential.